Pelatihan Membentuk Akuntan Berjiwa Kepemimpinan dan Berintegritas - Alfizi Alfizi; Giovanny Kristianto; RR Farida Istiningrum; Lusi Yuliarti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The profession of an accountant is one of the many promising occupations in the future that is needed by many companies. Apart from possessing the ability to solve the financial problems of a company, accountants are required to have leadership qualities and integrity in carrying out their tasks. The integrity of an accountant is demonstrated by their objectivity in work, which does not favor any interested party, ensuring the credibility of their work. These skills should be nurtured from an early age. Schools and universities can serve as a means to achieve this, so that training activities can foster students' confidence to work well in the future and be prepared to face the challenges of the workplace and the issues that may arise in the accounting profession.